Design and Evaluation of a Virtual Urology Sub-Internship During the COVID-19 Pandemic - Khoei, Amelia A.; Stocks, Blair T.; Zhuo, Jerry; Mayer, Wesley A.; Coburn, Michael; Hubbard, Caroline; Taylor, Jennifer M. (Frontiers in Urology, 2022)
Objective To offer learning opportunities to medical students during the pandemic and address technical challenges for operating room involvement, the Scott Department of Urology at the Baylor College of Medicine designed and evaluated a 2-week virtual elective course. Materials and Methods A manual for a virtual sub-internship was created by members of the Society of Academic Urologists, structured around core competencies. Our curriculum incorporated the manual to design a virtual experience. The course combined live surgical case streaming, one-on-one didactics, and virtual participation during in-person clinic sessions. The surgical streaming was enabled through a nominal investment of $150 for equipment. A post-course evaluation was distributed to participating students. Results The course evaluation received a 91% response rate from 11 enrolled fourth-year medical students. There was a very high level of satisfaction with the quality of the educational experience (M=5.8 +/-0.4). Open comments on course strengths highlighted the surgical streaming aspect of the experience, and 80% of evaluation respondents reported that one-on-one time with physicians was a strength of the virtual format. Conclusions Our curriculum effectively engaged medical students during a 2-week virtual urology elective. The surgical video streaming format is unique even among virtual rotations nationwide and may be adapted for any learners within or beyond an institution. Our curriculum provides an example for programs to incorporate these inexpensive streaming techniques and for students to gain exposure in their surgical areas of interest.